2010
DOI: 10.1016/j.mri.2010.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity between task-positive and task-negative brain areas and its relation to working memory performance

Abstract: Functional brain imaging studies have identified a set of brain areas typically activated during cognitive tasks (task-positive brain areas) and another set of brain areas typically deactivated during cognitive tasks (task-negative brain areas). Negative correlations, or anticorrelations, between taskpositive and task-negative brain areas have been reported at rest. Furthermore, the strength of these anticorrelations appears to be related to cognitive function. However, studies examining anticorrelations have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
242
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(269 citation statements)
references
References 20 publications
26
242
1
Order By: Relevance
“…During task performance it has been observed that task relevant networks (task-positive) exhibit increased activity, whereas networks associated with task irrelevant or opposing (tasknegative) processes show decreased activity. Strong anti-correlations between task-positive and task-negative networks have been shown to be predictive of cognitive task performance, including working memory (Hampson et al, 2010). Interestingly, anodal tDCS reduced task-…”
Section: Neural Enhancement Costmentioning
confidence: 99%
“…During task performance it has been observed that task relevant networks (task-positive) exhibit increased activity, whereas networks associated with task irrelevant or opposing (tasknegative) processes show decreased activity. Strong anti-correlations between task-positive and task-negative networks have been shown to be predictive of cognitive task performance, including working memory (Hampson et al, 2010). Interestingly, anodal tDCS reduced task-…”
Section: Neural Enhancement Costmentioning
confidence: 99%
“…Color image is available online at www.liebertpub.com/neu implicated extensively in a network important for selecting salient stimuli and guiding behavior in coordination with multiple other brain systems, [68][69][70] and the structural integrity of this network has been found to be crucial for DMN functioning in severe TBI. 71 Given that concurrent modulations of the DMN and task-positive regions have been found to support task performance in healthy individuals, [72][73][74][75] an increase in antiphase synchrony during the clinical recovery period may signify a restoration of balanced network function necessary for efficient cognitive processing. In keeping with the view of the DMN and TPN as reciprocal networks, co-occurring internetwork (PCC-TPN) antiphase synchrony and residual intranetwork (PCC-DMN) synchrony may be two parts of a larger effect involving the modulation and optimal balancing of distributed networks.…”
Section: Venkatesan Et Almentioning
confidence: 99%
“…A study by Kelley and colleagues (2008) suggests that task performance, in the sense of low intraindividual variability, does benefit from a negative correlation between activity in the task-negative and task-positive networks during engagement in a task. However, methodological issues concerning the analysis of strength and direction of such correlations are currently a matter of debate (Hampson, Driesen, Roth, Gore, & Constable, 2010;Murphy, Birn, Handwerker, Jones, & Bandettini, 2009). A more recent study by Gordon, Stollstorff, Devaney, Bean, and Vaidya (2011) characterized connectivity only in relative terms: these authors found a dopaminergic effect on connectivity between the taskpositive and task-negative networks.…”
Section: Testing the Dimensional Approach Of Cognitive Flexibility Anmentioning
confidence: 99%